Corruption-Economic Growth In Eight Emerging Asian Economies - Ali, Imran (2022)
This research is an attempt to find the direct and indirect impact of corruption on economic growth with the sample size of eight Asian countries namely Bangladesh, China, India, Indonesia, Malaysia, Pakistan, Sri-Lanka, and Thailand. For the indirect impact, this research has used six economic indicators namely through private investment, human capital, law and order, bureaucratic quality, international trade, and political stability. To achieve this objective, this research has used the Newey West Standard Error technique to handle the autocorrelation and heteroscedasticity problem in the model. The results of this research have confirmed corruption has an adverse impact on economic growth through private investment, human capital, international trade, and political stability. Moreover, the estimated results have also confirmed that as corruption level is decreasing the quality of bureaucracy is also increasing but that improvement in bureaucracy has a negative impact on economic growth. Secondly, through the law-and-order, this research has confirmed that as corruption is decreasing, the law-and-order situation is improving which ultimately has a positive impact on the growth rate. Furthermore, this research has explored the long-run relationship (causality) between corruption and these six economic indicators because corruption is a long-run challenge it needs decades to make the country corruption-free and this research is more interested to know the longevity of impact of corruption on these economic indicators.